Strictly speaking, x^2 + 2x + 4 doesn't have solutions; if you want solutions, you must equate <span>x^2 + 2x + 4 to zero:
</span>x^2 + 2x + 4= 0. "Completing the square" seems to be the easiest way to go here:
rewrite x^2 + 2x + 4 as x^2 + 2x + 1^2 - 1^2 = -4, or
(x+1)^2 = -3
or x+1 =i*(plus or minus sqrt(3))
or x = -1 plus or minus i*sqrt(3)
This problem, like any other quadratic equation, has two roots. Note that the fourth possible answer constitutes one part of the two part solution found above.
Answer: NONE
<u>Step-by-step explanation:</u>
Consider that m is the degree of the numerator and n is the degree of the denominator.
The rules for horizontal asymptote (H.A.) are as follows:
If m > n then no H.A. (use long division to find the slant asymptote)
If m = n then H.A. is y = leading coefficient of numerator/leading coefficient of denominator
If m < n then H.A. is y = 0
Given: g(x) = 5x⁵/(x³ - 2x + 1)
--> m = 5, n = 3
Since m > n then there is no H.A.
Subtract 24.45 from itself the subtract 13.27 by 24.45 and should t=37.73
Answer: n = -3
Step-by-step explanation:
8(3n + 5) = -32
- <em>Divide both sides by 8.</em>
(3n + 5) = -4
- <em>Subtract 5 by both sides.</em>
3n = -4 - 5
3n = -9
- <em>Divide both sides by 3.</em>
n = -3